Sexual dysfunction in inflammatory bowel disease: What the specialist should know and ask - de Arce, Edith Perez; Quera, Rodrigo; Barros, Jaqueline Ribeiro [UNESP]; Sassaki, Ligia Yukie [UNESP] (Taylor & Francis, 2021)
Inflammatory bowel disease (IBD) is a chronic condition that globally affects the health of people who suffer from it, deteriorating their quality of life (QoL). An aspect rarely explored by healthcare providers is the influence of the disease on the sexual functioning of individuals. This discretion is mainly due to an unconscious resistance when asking our patients about their sexual functioning because of a lack of knowledge and skills to tackle this topic or disinterest on the part of professionals, and fear or shame on the part of patients. Sexual function is a constant concern in IBD patients that has been reflected in several studies, especially if we consider that the prevalence of sexual dysfunction (SD) in IBD is higher than that reported in the general population. The etiology of SD in patients with IBD remains unclear but is likely to be multifactorial, where biological, psychosocial, and disease-specific factors are involved. Currently, there are no formal recommendations in the IBD clinical guidelines on how to manage SD in these patients. The use of validated clinical scales could improve the detection of SD and allow the treatment of the underlying causes in order to improve the QoL of patients with IBD. This review aims to illustrate the different aspects involved in SD in IBD patients and the importance of the participation of a multidisciplinary team in the early detection and treatment of SD at different stages of the disease.
Keywords: Crohn's disease; Inflammatory bowel disease; Sexual dysfunction; Ulcerative colitis